(untitled) (Bangladesh Journal of Medical Science, 2018)
Bilateral congenital mesotympanic cholesteatoma is a very rare disease. It can present differently from ordinary congenital cholesteatoma. We report a case of bilateral congenital cholesteatoma diagnosed at age of 22 years old. She presented with bilateral intermittent ear discharge since 10 years old that worsening two weeks prior to her presentation to our clinic and associated with bilateral reduced hearing. Clinically there was intact tympanic membrane with retraction of the mesotympanic area with present of mass medial to tympanic membrane. CT scan imaging showed there was soft tissue in the bilateral middle ear cavity with intact scutum and ossicles. Patient undergone canal wall down procedure and the diagnosis of congenital mesotympanic cholesteatoma was confirmed with present of cholesteatoma sac at the posterosuperior part, as opposed to anterosuperior quadrant, where the common site for congenital cholesteatoma. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.307-310